A sociolinguistic analysis of graffiti written in Shona and English found in selected urban areas of Zimbabwe - Mangeya, Hugh (University of South Africa, 2016)
Submitted in accordance with the requirements for the degree of DOCTOR OF LITERATURE AND PHILOSOPHY in the subject of AFRICAN LANGUAGES at the UNIVERSITY OF SOUTH AFRICA